Effects of elevated ozone concentration on yield of four Chinese cultivars of winter wheat under fully open-air field conditions - ZHU, XINKAI; FENG, ZHAOZHONG; SUN, TAOFANG; LIU, XIAOCHENG; TANG, HAOYE; ZHU, JIANGUO; GUO, WENSHAN; KOBAYASHI, KAZUHIKO (Global change biology, 2011)
Four modern cultivars of winter wheat (Triticum aestivum L.) were grown under elevated ozone concentration (E-O₃) in fully open-air field conditions in China for three consecutive growth seasons from 2007 to 2009. Results indicated that a mean 25% enhancement above the ambient ozone concentration (A-O₃, 45.7 p.p.b.) significantly reduced the grain yield by 20% with significant variation in the range from 10% to 35% among the combinations of cultivar and season. The varietal difference in the yield response to E-O₃ became nonsignificant when the anova was done by omitting one cultivar which showed unstable response to E-O₃ among the seasons. The reduction of individual grain mass accounted mostly for the yield loss by E-O₃, and showed significant difference between the cultivars. The response of relative yield to E-O₃ was not significantly different from those reported in China, Europe and India on the basis of experiments in open-top chambers. Our results thus confirmed the rising threat of surface O₃ on wheat production worldwide in the near future. Various countermeasures are urgently needed against the crop losses due to O₃ such as mitigation of the increase in surface O₃ with stricter pollution control, and enhancement of the wheat tolerance against O₃ by breeding and management.